Effect of Early vs. Late Maturing Sire Lines and Creep Feeding on the Stress Response, Intestinal Permeability, and Growth Performance of Nursery and Finishing Pigs - Madie R. Wensley; Jason C. Woodworth; Mike D. Tokach; Robert D. Goodband; Joel M. DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2022)
A total of 21 litters (early or late maturing Duroc × DNA 241) and 247 pigs were used in 170-d trial to determine the effect of sire line growth pattern (early vs. late maturing) and creep feeding on the stress response, intestinal permeability, and growth performance of nursery and finishing pigs.Treatments were arranged in a 2 × 2 factorial with main effect of Duroc sire line (early or late maturing) and lactation creep feeding (with or without). Immediately after weaning (initially 14.0 lb), blood cortisol levels were increased (P<0.01) in late maturing pigs compared to early maturing pigs, indicating an increased stress response. A greater percentage (P<0.001) of late maturing pigs lost weight from d 0 to 3 post-weaning compared to early maturing pigs. Likewise, early maturing pigs had improved ADG (P<0.001) and ADFI (P<0.001) during the first 3 d in the nursery. A similar response was observed in daily feed intake with early maturing pigs having increased daily feed intake (P<0.001) for the first 14 d in the nursery. However, no differences were observed in intestinal permeability between treatments. For overall nursery growth performance, a significant interaction was observed for ADG (P= 0.007) and ADFI (P<0.001). Early maturing pigs that did or did not receive creep feed had increased ADG and ADFI compared to late maturing pigs that did not receive creep feed, with late maturing pigs that received creep feed intermediate. For overall nursery feed efficiency, early maturing pigs had poorer F/G (P<0.001) than late maturing pigs. For overall finishing growth performance, a significant interaction was observed for ADG (P= 0.007), with late maturing pigs that received creep feed prior to weaning having increased ADG compared to the other 3 treatment combinations. A significant interaction was also observed for ADFI (P<0.007), with late maturing pigs that received creep feed or early maturing pigs having increased ADFI compared to late maturing pigs that did not receive creep feed. This resulted in a significant interaction for final BW (P= 0.005), with late maturing pigs that did not receive creep feed having decreased weights at market. In summary, early maturing pigs had improved ADG and ADFI until approximately 220 lb, at which point late maturing pigs began to exhibit improved ADG. Late maturing pigs also had improved feed efficiency throughout much of the experiment. Interestingly, creep feeding the late maturing pigs resulted in improved growth performance compared to providing no creep feed, whereas creep feed did not impact the early maturing pigs.
Keywords: creep feed; finishing pig; growth performance; nursery pig; sire line